Isolation and Identification of Bacteria from Weaver Ants (Oecophylla smaragdina) - Livia Juniati (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Purpose: Weaver ants (O.smaragdina) are the most frequently encountered ants in the surrounding environment and certainly have an important role, one of which is as a producer of antimicrobial compounds. Microbes are found naturally in mixed populations and to obtain pure cultures, microbial isolation can be carried out. This study aims to isolate bacteria from O.smaragdina from the head, body and tail. Methods: Bacterial isolation from O.smaragdina was carried out macroscopically and microscopically. Results: The results showed that macroscopically there were 6 bacterial isolates. Then microscopically the 6 isolates belong to the gram-positive bacteria. Also obtained 6 isolates with bacillus form.